2018
DOI: 10.1525/abt.2018.80.7.493
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Student Learning on Emerging Infectious Diseases: An Ebola Exemplar

Abstract: Throughout global history, various infectious diseases have emerged as particularly relevant within an era. Some examples include the Bubonic plague of the fourteenth century, the Spanish Influenza pandemic of 1918, the HIV epidemic of the 1980s, and the Zika virus outbreak in 2015–16. These instances of emerging infectious disease represent ideal opportunities for timely, relevant instruction in natural and health science courses through case studies. Such instructional approaches can promote student engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Thirteen out of forty-six studies (28%) used traditional didactics such as lectures and other adult learning strategies including interactive group and learner-led discussions, 52 54 61 case-based learning, 29 55 problem-based learning, 48 demonstrations/return demonstrations 41 49 and role playing. 49 54 Most of the studies that aimed to convey theoretical knowledge consisted of brief sessions, that is, less than a day (n=8/13, 62%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen out of forty-six studies (28%) used traditional didactics such as lectures and other adult learning strategies including interactive group and learner-led discussions, 52 54 61 case-based learning, 29 55 problem-based learning, 48 demonstrations/return demonstrations 41 49 and role playing. 49 54 Most of the studies that aimed to convey theoretical knowledge consisted of brief sessions, that is, less than a day (n=8/13, 62%).…”
Section: Resultsmentioning
confidence: 99%
“…More closely related to the current pandemic, in a survey of over 500 United States high school science teachers, 76% indicated that they discussed Ebola as part of their curriculum during the 2014 Ebola outbreak, and that an important factor in the decision to cover Ebola was student interest in the topic (Smith, Torsiglieri, Keith Esch, & Pasley, 2017). Relatedly, in an undergraduate biology class that utilized a case study approach to Ebola and virology, students reported high levels of interest and showed decreased misconceptions about viruses and Ebola (Dube, Addy, Teixeira, & Iadarola, 2018). Considered collectively, prior research from allied fields indicates that incorporating a current event into the classroom may promote learning by facilitating higher levels of interest and engagement.…”
mentioning
confidence: 99%